Deletion of the L-Lactate Dehydrogenase Gene ldh in Streptococcus pyogenes Leads to a Loss of SpeB Activity and a Hypovirulent Phenotype - Oehmcke-Hecht, Sonja; Nass, Leif E.; Wichura, Jan B.; Mikkat, Stefan; Kreikemeyer, Bernd; Fiedler, Tomas (Frontiers in Microbiology, 2017)
Streptococcus pyogenes uses lactic acid fermentation for the generation of ATP. Here, we analyzed the impact of a deletion of the L-lactate dehydrogenase gene ldh on the virulence of S. pyogenes M49. While the ldh deletion does not cause a general growth deficiency in laboratory media, the growth in human blood and plasma is significantly hampered. The ldh deletion strain is furthermore less virulent in a Galleria mellonella infection model. We show that the ldh deletion leads to a decrease in the activity of the cysteine protease SpeB, an important secreted virulence factor of S. pyogenes. The reduced SpeB activity is caused by a hampered autocatalytic activation of the SpeB zymogen into the mature SpeB. The missing SpeB activity furthermore leads to increased plasmin activation and a reduced activation of the contact system on the surface of S. pyogenes. All these effects can be reversed when ldh is reintroduced into the mutant via a plasmid. The results demonstrate a previously unappreciated role for LDH in modulation of SpeB maturation.